AI Risk Management: A Bibliometric Analysis - Adelaide Emma Bernardelli; Paolo Giudici (Risks)
The growth of Artificial Intelligence applications requires the development of risk management models that can balance opportunities with risks. This paper contributes to the development of Artificial Intelligence risk management models by means of a thorough bibliometric analysis. The analysis highlights the need to develop a quantitative AI risk management framework.